Multifunctional chitosan/polyvinyl pyrrolidone/45S5 Bioglass® scaffolds for MC3T3-E1 cell stimulation and drug release - Yao, Qingqing; Li, Wei; Yu, Shanshan; Ma, Liwei; Jin, Dayong; Boccaccini, Aldo R.; Liu, Yong (Materials Science and Engineering C, 2015)
Abstract Novel chitosan-polyvinyl pyrrolidone/45S5 Bioglass® (CS-PVP/BG) scaffolds were prepared via foam replication and chemical cross-linking techniques. The pristine BG, CS-PVP coated BG and genipin cross-linked CS-PVP/BG (G-CS-PVP/BG) scaffolds were synthesized and characterized in terms of chemical composition, physical structure and morphology respectively. Resistance to enzymatic degradation of the scaffold is improved significantly with the use of genipin cross-linked CS-PVP. The bio-effects of scaffolds on MC3T3-E1 osteoblast-like cells were evaluated by studying cell viability, adhesion and proliferation. The CCK-8 assay shows that cell viability on the resulting G-CS-PVP/BG scaffold is improved obviously after cross-linking of genipin. Cell skeleton images exhibit that well-stretched F-actin bundles are obtained on the G-CS-PVP/BG scaffold. SEM results present significant improvement on the cell adhesion and proliferation for cells cultured on the G-CS-PVP/BG scaffold. The drug release performance on the as-synthesized scaffold was studied in a phosphate buffered saline (PBS) solution. Vancomycin is found to be released in burst fashion within 24 h from the pristine BG scaffold, however, the release period from the G-CS-PVP/BG scaffold is enhanced to 7 days, indicating improved drug release properties of the G-CS-PVP/BG scaffold. Our results suggest that the G-CS-PVP/BG scaffolds possess promising physicochemical properties, sustained drug release capability and good biocompatibility for MC3T3-E1 cells' proliferation and adhesion, suggesting their potential applications in areas such as MC3T3-E1 cell stimulation and bone tissue engineering.
Keywords: 45S5 Bioglass®; Chitosan; Drug release; MC3T3-E1 cells; Polyvinyl pyrrolidone; Scaffolds